Real world experience with minimally invasive wireless percutaneous neuromodulation in a tertiary care centre. Issue 4 (August 2022) - Pushparaj, Hemkumar; Chawla, Rajiv; Bhargava, Deepti; Biswas, Shubhabrata; Sharma, Manohar L
Background: Wireless percutaneous nerve stimulation (PNS) for chronic pain is rapidly evolving in the ever expanding neuromodulation paradigm. Safety and lower risks with a potential of long-term analgesia cannot be over emphasised especially with the ongoing opioid pandemic. PNS with an implanted pulse generator (IPG) has also been shown to provide good benefit, without often unpleasant widespread paraesthesia from conventional spinal cord stimulators. Aim and Methods: We retrospectively extracted data on all wireless PNS implants in our highly specialised pain neuromodulation centre since initiation of wireless PNS service in August 2019. Patient demographics, pain history, analgesic intake and details on implant follow-up data within 1 year post-implant including pain relief, EuroQol-5 Dimension (EQ-5D) and Patients' Global Impression of Change (PGIC) scores were extracted. The cases are presented in a narrative format. Result: A total of five patients were implanted with wireless (Stimwave ® ) PNS from August 2019 to February 2020. Neuropathic pain was the most common presenting diagnosis. All patients showed >50% pain relief at 3 months. EQ-5D and PGIC did not show any improvement in the subjects. Two of the patients managed to decrease their analgesics after implantation. Similar sustained benefits could not be demonstrated after 1 year. Discussion: PNS can provide analgesia in appropriately selected cases. Naivety of the technique and procedure might cause some degree of uncertainty. External pulse generator with wireless transmission avoids IPG and tunnelling related side effects, but requires individualised special wearable technology to power the lead. Minimally invasive nature of the technique might be attractive and preferable for patients with complex medical issues, nickel allergy and poor general health who may otherwise be unsuitable for Spinal Cord Stimulation (SCS) with conventional hardware. Robust prospective controlled studies and RCTs in future might provide further insights on utility in other neuropathic pain diagnosis, long-term outcomes and acceptability compared to conventional SCS.